Task-Based Language Teaching (TBLT) for English Class in Indonesia - Efriza, Dony; Zainil, Yetti; Syarif, Hermawati; Zaim, M. (Proceedings International Conference on Education Innovation and Social Science, 2023)
The principal objective of English language instruction in Indonesia is to furnish Indonesian pupils with the ability to communicate effectively in English. The English communicative skills of Indonesian school graduates have been found to be low, which can be attributed to the prevalent use of traditional student-centered approaches that emphasise linguistic structural properties. Additionally, the lack of exposure to and usage of the target language in the classroom further contributes to this issue. A limited number of students possess the ability to effectively convey concepts, perspectives, and emotions utilising English as a means of interaction. The objective of this review article is to advocate for the effectiveness of the task-based language teaching (TBLT) approach in enhancing the communicative abilities of students in Indonesia. This paper utilises various theoretical frameworks and empirical studies to undertake a critical examination of the advantages and drawbacks associated with the implementation of Task-Based Language Teaching (TBLT) in Indonesia. The argument posits that Task-Based Language Teaching (TBLT) facilitates organic learning, engenders inherent motivation among students, and fosters the development of language skills, which may result in an expedited enhancement of communicative proficiency.